Image retrieval with a virtual reality interface. - Wong, Tsui Pyng. (2008)
Most research in image retrieval focus on devising new techniques to extract relevant image clues through the use of complex algorithms. In this study, a different approach will be taken. Instead of looking at ways to index and extract images, we will look at how a user interface can help to improve the search process. This prototype makes use of textual descriptions to present a simple and logical way in retrieving images. In addition, this study also looks into ways to present retrieved results. Research in image retrieval has overlooked the importance of having a user-oriented interface and the presentation of retrieved results. In this study, a web-based client/server prototype for interactive search that allows the users to input and refine their search terms is presented. Once a set of images meeting the users' queries has been identified, the system will dynamically build a virtual environment that allows users to explore and view these images interactively at their own pace. The display of the images exploits VRML technology. This study also includes examining whether the use of desktop virtual reality will help users in lightening their cognitive overheads and provides a better presentation of the retrieved results.